ICT Intervention-Research in a mental health clinic in Brazil - Maraschin, Cleci; Rocha, Marisa Lopes da; Kastrup, Virginia (Revista Polis e Psique, 2015)
Abstract This article discusses the use of intervention-research as a qualitative method that aims to explore how knowledge production can be affected and transformed by an intervention. We describe and examine four levels of reflexive feedback within an intervention experience using information and communication technology (ICT) workshops in a mental health clinic for children and adolescents in Porto Alegre/Brazil. It is argued that an intervention can generate a rich reflexive experience which can challenge the research group’s misconceptions, the participants’ reflexive notions, institutional common sense and the research directions. It can be said that the methodology also enables the exploration of new capacities and emotions not only by children and teenagers, but by everyone involved. Keywords: Intervention-Research; Qualitative Research Methods; ICT Workshops; Mental Care. Resumo O presente artigo discute o uso da pesquisa-intervenção como um método qualitativo que tem por objetido explorar como a produção de conhecimento pode ser afetada e transformada pela intervenção. Em particular, descreve e analisa quatro níveis de retroalimentação reflexiva em uma experiência de intervenção utilizando oficinas de tecnologias de informação e comunicação (TIC) em um serviço de saúde mental para crianças e jovens de Porto Alegre/Brasil. Argumenta que a pesquisa-intervenção pode oferecer uma importante experiência reflexiva que questiona as concepções da equipe de pesquisa, as noções dos participantes e o senso-comum institucional e todos esses fatores podem deslocar as direções da pesquisa. A metodologia também permite a exploração de novas capacidades e emoções, não somente para crianças e jovens, mas para todos os envolvidos no processo. Palavras-chave: Pesquisa-Intervenção; Metodologia Qualitativa; Oficinas com TIC; Saúde Mental.